EVALUATION OF THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS IN THE INTENSIVE CARE UNIT OF SUNAN KUDUS ISLAMIC HOSPITAL - Listiana Dewi Sartika; Erliany Syaodih; Yani Restiani Widjaja (Universitas Muhammadiyah Kudus, 2024)
An electronic medical record (RME) is a real-time, patient-centered medical record that provides information directly and securely to authorized users. With the novelty of RME in the health world, there are still not many studies that address the evaluation of RME in various aspects. This study is to determine the results of the evaluation of RME implementation in terms of roles, programs, regulations obj, objectives/ideal conditions, and hospital income. This study is a qualitative descriptive study. The method used is the interview—data processing with data reduction, organization, and interpretation. The data processing process is processed descriptively. The research was conducted in the Intensive Care Unit (ICU) of Sunan Kudus Islamic Hospital for 4 months from February to June 2024. Sampling technique with purposive sampling to officers related to medical records as many as 4 participants. Inclusion criteria are officers who manage medical records, patient service managers, and case mix. Exclusion criteria: refused to participate in the study. The results showed that RME is running well and has a positive influence in the ICU in terms of roles/functions, programs, regulations, expected goals, and income generation. In the role/function aspect, the informants have carried out their duties well in supporting RME. In the aspect of the program, it has been running well in accordance with the provisions; in the aspect of regulations, there is an SPO RME; in the aspect of goals, RME is beneficial for improving services even though several ideal conditions have not been achieved. In terms of revenue, implementing RME plays a role in increasing hospital revenue. The ideal conditions expected are continuous improvement and socialization through RME and health technology development.